Facing the death penalty : essays on a cruel and unusual punishment - Radelet, Michael L. (Temple University Press, 1989)
"These essays ... show us the human and inhuman realities of capital punishment through the eyes of the condemned and those who work with them. By focusing on those awaiting death, they present the awful truth behind the statistics in concrete, personal terms." â€"William J. Bowers, author of Legal HomicideBetween 1930 and 1967, there were 3,859 executions carried out under state and civil authority in the United States. Since the ten-year moratorium on capital punishment ended in 1977, more than one hundred prisoners have been executed. There are more than two thousand men and women now